DOI: 10.31274/rtd-180813-4551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reciprocal full-sib selection in maize

Abstract: This reproduction was made from a copy of a manuscript sent to us for publication and microfilming. While the most advanced technology has been used to pho tograph and reproduce this manuscript, the quality of the reproduction is heavily dependent upon the quality of the material submitted. Pages in any manuscript may have indistinct print. In aU cases the best available copy has been filmed.The following explanation of techniques is provided to help clarify notations which may appear on this reproduction.1. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This result agreed with theory in that smaller effective population sizes were used for half-sib and SI family selection relative to mass selection and the smaller population sizes should result in increased genetic drift and decreased genetic variance. Reeder (1985) evaluated progress from six cycles of reciprocal full-sib recurrent selection in the BS10 and BSll com populations. He reported that additive genetic variance tended to decrease for yield, stalk lodging, ear and plant height from the CO to the C6.…”
Section: Literature Review Ihtrapopulaiion Reoirrait Sdectimmentioning
confidence: 99%
“…This result agreed with theory in that smaller effective population sizes were used for half-sib and SI family selection relative to mass selection and the smaller population sizes should result in increased genetic drift and decreased genetic variance. Reeder (1985) evaluated progress from six cycles of reciprocal full-sib recurrent selection in the BS10 and BSll com populations. He reported that additive genetic variance tended to decrease for yield, stalk lodging, ear and plant height from the CO to the C6.…”
Section: Literature Review Ihtrapopulaiion Reoirrait Sdectimmentioning
confidence: 99%